Two Limonoids from The Seeds of Chisocheton Macrophyllus and Their Cytotoxic Activity Against Mcf-7 Breast Cancer Cells - Intan Rahmayanti; Nurlelasari Nurlelasari; Desi Harneti; Rani Maharani; Darwati Darwati; Yoshihito Shiono; Unang Supratman (Molekul, 2021)
Limonoids (tetranortriterpenoids) are triterpenoid compounds that lose four terminals in their structural framework. These compounds have a wide variety of structures and interesting activities including anti-inflammatory, anti-cancer, anti-tumor and anti-malarial properties. The purpose of this study was to find limonoid compounds from the Indonesian Chisocheton plant, and one of which is Chisocheton macrophyllus. The dried and powdered seeds of C. macrophyllus (4.5 kg) were extracted with methanol and partitioned successively with n-hexane, ethyl acetate and n-butanol. Evaporation of each extract resulted in the crude extracts of n-hexane (346.6 g), ethyl acetate (60.8 g) and n-butanol (14.6 g). The n-hexane fraction was subjected to a silica gel vacuum-liquid chromatography (VLC) column packed with silica gel 60 using gradient of n-hexane, ethyl acetate and methanol (10% stepwise) to afford thirteen fractions (A-M). Fraction F (4.4 g) was subjected to silica gel column chromatography using gradient of n-hexane and ethyl acetate (5% stepwise). Subfraction F5 (1.2 g) was chromatographed on a column of silica gel eluted with n-hexane: CH2Cl2: EtOAc (2:7.5:0.5) to give compound 1 (19.7 mg) and fraction H (1.8 g) was subjected to silica gel column chromatography using gradient of n-hexane and ethyl acetate (5% stepwise) as eluting solvent to give 2 (12.0 mg). Chemical structures of 1 and 2 were elucidated by spectroscopic methods and determined as 6α-acetoxyepoxyazadiradione (1) and Dysobinin(2). Dysobinin (2) showed weak cytotoxic activity against MCF-7 breast cancer cells with an IC50 value of 228.15 μM